EFFORTS TO INCREASE LEARNING MOTIVATION USING THE ECONOMIC TOKEN TECHNIQUE IN TAMANSURUH DSN RT/03 RW/01 DS BANGOREJO KEC BANGOREJO KAB BANYUWANGI - Miftahul Arifin; Bangun Firmansyah (MAN Insan Cendekia Jambi, 2022)
Motivation comes from the word motive which can be interpreted as the driving force that exists within a person to carry out certain activities in order to achieve a goal. Motivation is the basic impulse that moves a person to act in achieving the desired goals. Motivation is a spirit that a person has in doing something for a specific purpose. Learning motivation is all the symptoms contained in the stimulation of action to generate, maintain and control the basic impulses in adolescents in achieving learning goals. Adolescents who have good learning motivation will be encouraged to do learning activities, but if they do not have motivation to learn, they will not do learning activities. The purpose of this study is to find out what factors affect the decline in learning motivation in adolescents during the pandemic and find out the results of the application of the token economy technique in increasing adolescent learning motivation during the pandemic. This research was conducted to prove that the application of the token economy technique can be applied to increase adolescent learning motivation during the pandemic. This research is a type of qualitative case study research, data collection is carried out by in-depth interviews, observation and documentation techniques. The subjects in this study amounted to one person, namely teenagers from Dsn. Tamansuruh RT/03 RW/01 Ds. Bangorejo district. Bangorejo, Banyuwangi Regency, which experienced a decrease in learning motivation, so it was necessary to give a treatment in order to experience an increase in learning motivation. The results of this study indicate that adolescents experience a decrease in learning motivation because it is influenced by two factors, namely intrinsic factors or internal factors that have a desire to play online games, the second factor is extrinsic factors or factors that influence through outside one's self where adolescents are influenced by situations and learning conditions during the pandemic so that the two factors above affect adolescents experience a decrease in learning motivation, a decrease in learning motivation in adolescents is applied to a technique to increase learning motivation, namely the token economy technique, where after the application of this technique a significant change appears, namely getting used to learning activities even already become a daily routine, have a schedule of learning activities, in learning the subject is always consistent at the hours usually used for studying, namely 18.30 to 19.30, have other activities as a transition from playing online games, namely studying and playing. fishing, in playing games the subject spent less time than before the technique was applied, namely 5 to 8 hours per day